The practical application of 3D vision in the field: measuring reindeer (Rangifer tarandus) antler growth velocities. (7th November 2016) - Lichti, Derek D.; Steward, Jeremy; Chow, Jacky C. K.; Matyas, John
Abstract: Advances in three‐dimensional (3D) optical imaging have made possible precise and accurate measurements of many scenes, ranging from engineering to architecture to art. However, measurements of some 3D objects are more difficult to obtain than others, particularly if the edges do not feature regular geometry, the colour is dark and variable, and if the object moves haphazardly. Such objects occur regularly in biology, and the present study illustrates some of the challenges of evaluating such objects. The growing antlers of three live reindeer ( Rangifer tarandus ) is presented as an example of how 3D imaging, specifically time‐of‐flight range imaging, can be used to solve to a reasonable extent a problem that is very difficult to approximate using traditional techniques. Mean antler growth velocities of the order of 7 to 9 mm/day were estimated, using the proposed methodology, from data of these three animals collected over a seven‐week period.